Revolutionizing Retail: A Mini Review of E-commerce Evolution - Ntumba, Charles; Aguayo, Samuel; Maina, Kamau (Journal of Digital Marketing and Communication, 2023)
This review article delves into the transformative journey of e-commerce, tracing its inception in the mid-1990s, characterized by visionary companies such as Amazon, eBay, Alibaba, PayPal, and Dell. These pioneers laid the foundation for a digital commerce revolution, with technological innovations, particularly in mobile technology, reshaping the e-commerce landscape and providing users with seamless, on-the-go shopping experiences. The integration of augmented reality (AR) and virtual reality (VR) further bridged the gap between physical and digital realms, offering immersive product interactions. Artificial intelligence (AI) emerged as a transformative force, utilizing algorithms to analyze user data and personalize online shopping experiences. AI-driven chatbots and virtual assistants enhanced customer support, contributing to an overall personalized shopping journey. The predictive capabilities of AI enabled platforms to anticipate user behavior and strategically deploy personalized recommendations. Evolving consumer behavior, influenced by the convenience of online shopping and social media, is a central theme, with the rise of conscious consumers emphasizing sustainability and ethical practices in purchasing decisions. Looking forward, future trends in e-commerce include the continued dominance of AI in refining personalization, the potential of blockchain for transparency and security, and the integration of the Internet of Things (IoT) for a more connected shopping experience. AR, VR, voice commerce, and cross-border e-commerce are anticipated to play significant roles.